ANCA-ASSOCIATED GLOMERULONEPHRITIS IN CHILDREN WITH JUVENILE RHEUMATOID ARTHRITIS - Борисова, Тамара; Самсоненко, Светлана; Бадогина, Людмила (SWorldJournal, 2020)
The literature review presents data on the mechanisms of development, clinical manifestations, diagnosis, treatment and outcomes of ANCA-associated glomerulonephritis in children with juvenile rheumatoid arthritis (JRA).ANCA-associated glomerulonephriti